Report on Status of Nurses in Nepal - Paudel, Kritika (2012)
Nursing is considered as caring profession. Traditionally nursing was considered as the service providing within four walls taking care of the sick, injured and dying person. With the advancement of time and improvement of the profession it included total care of the patients and healthy people. These days the profession has expanded from hospital to community and many other places such as schools, hotels, offices etc. The scope of nursing has increased with more emphasis and priority on preventive and promotional aspect of health care. Similarly, the preventive and promotional nursing are in global priority. It seems that it is difficult to meet the need for the global demand of nursing and becoming shortage especially in western world and gulf countries. Similarly, in developing countries like Nepal nursing profession is becoming highly demanding and young students are attracted to the nursing profession due to endless opportunities around the world. Hence this study concentrates on the overall status of nurses in Nepal. It focuses on the nursing policy, nursing services, structure of nursing education, as well as current situation of nurses and its scope and problems encountered by the nurses in Nepal. This is a descriptive study using primary and secondary data. Key informant interviews were conducted for the purpose of primary data collection whereas available records and reports were reviewed for secondary data collection.